Czy proca znaleziona w Gdańsku jest zabawką? - Nadolska, Krystyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
The article treats a unique of early medieval sling-shat found in Gdańsk. This item has been classified in the archaeological literature as a children’s toy. Its size as well the features of construction, however, are close to the items considered as a weapon. Further the author discusses the suitability of this kind of weapon in battle and in hunting, and arrives at the conclusion that it is more functional as a hunting weapon, but its being used in the battle can not be excluded.